Interventionalist Perspective on the New Endovascular Trials. Issue 6 (June 2015) - Pierot, Laurent; Derdeyn, Colin
Abstract : Three recently published trials have conclusively proven the benefit of mechanical endovascular thrombectomy over best medical therapy for patients with acute ischemic stroke and large vessel occlusion. These trials shared some features and differed in others. These similarities and differences in trial design and execution affect the conclusions and recommendations that can be made from the data. We will examine the implications of these studies for neurointerventionists, both for current practice and for future studies. In particular, we will focus on procedural details such as patient selection, devices, adjunctive therapies, treatment time windows, and performance metrics.